The role of gadgets in modern education - Zayniddinova, Shahnoza (MMIT Proceedings, 2025)
This article shows what place modern education occupies in our lives today. As we know, the modern education system keeps pace with the times. New technologies and teaching methods also occupy this position. Moreover, it is impossible to imagine a perfect picture of the educational process without modern equipment. In this article, we will also look at how education has changed to a modern style.